Sharing of common proteins by the stages of the tick, Hyalomma anatolicum anutolicum and Boophilus microplus - GHOSH, S; KHAN, M H (The Indian Journal of Animal Sciences, 2013)
Sharing of common proteins was studied between the stages of Hyalomma anatolicum and Boophilus mieroplus. SDSÂ·PAGE revealed common proteins of molecular weights of 68, 57.5, 50.8,47.3,43 and <43 kDa in all the stages of these 2 species of ticks.